2007
DOI: 10.1097/mjt.0b013e3180325905
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin-Induced Skin Necrosis: A Fatal Outcome

Abstract: Enoxaparin, a low-molecular-weight heparin used to treat and prevent deep venous thrombosis, has been evaluated in several clinical trials. Thrombosis induced by enoxaparin with no evidence of heparin-induced thrombocytopenia (HIT) is seldom described. We report a rare case in which an 89-year-old African-American female developed large, multiple, painful lesions induced by enoxaparin administration. Laboratory investigations for HIT, disseminated intravascular coagulation, protein C, protein S, factor V, fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
1
6
0
1
Order By: Relevance
“…Along with bleeding risk, rare cutaneous side effects have been reported in the literature [2] , [3] . Enoxaparin-induced skin necrosis, as seen in our case, has been associated with grave consequences, including death [4] , [5] .…”
Section: Introductionsupporting
confidence: 52%
“…Along with bleeding risk, rare cutaneous side effects have been reported in the literature [2] , [3] . Enoxaparin-induced skin necrosis, as seen in our case, has been associated with grave consequences, including death [4] , [5] .…”
Section: Introductionsupporting
confidence: 52%
“…According to the published reports the patients who developed this type of condition were treated successfully with local excision [6]- [9]. In one single previous report the outcome was fatal [10]. In our patient the necrotic tissue was the source of sepsis and ultimately with the fatal consequence.…”
Section: Discussionmentioning
confidence: 69%
“…Unlike our study, results from a nested case–control study conducted on AF patients using the UK Clinical Practice Research Datalink supported this theory, since Azoulay et al found a 71% increased risk of stroke in the first 30 days of warfarin use compared with nonuse, whereas a decreased risk was observed after 30 days of use 45. However, this theory does not justify the routine use of bridging therapy since VKA‐induced skin necrosis occurs mostly in patients with inherited or acquired thrombophilia, such as protein C or S deficiencies,44 and several case studies have also reported that LMWH can also lead to skin necrosis 46, 47. Lastly, there is insufficient evidence justifying systematic use of bridging therapy.…”
Section: Discussionmentioning
confidence: 99%